Injectable FHE+BP composites hydrogel with enhanced regenerative capacity of tendon-bone interface for anterior cruciate ligament reconstruction - Cho, Eunshinae; Qiao, Yi; Chen, Changan; Xu, Junjie; Cai, Jiangyu; Li, Yamin; Zhao, Jinzhong (Frontiers in Bioengineering and Biotechnology, 2023)
Features of black phosphorous (BP) nano sheets such as enhancing mineralization and reducing cytotoxicity in bone regeneration field have been reported. Thermo-responsive FHE hydrogel (mainly composed of oxidized hyaluronic acid (OHA), poly-ε-L-lysine (ε-EPL) and F127) also showed a desired outcome in skin regeneration due to its stability and antibacterial benefits. This study investigated the application of BP-FHE hydrogel in anterior cruciate ligament reconstruction (ACLR) both in in-vitro and in-vivo, and addressed its effects on tendon and bone healing. This BP-FHE hydrogel is expected to bring the benefits of both components (thermo-sensitivity, induced osteogenesis and easy delivery) to optimize the clinical application of ACLR and enhance the recovery. Our in-vitro results confirmed the potential role of BP-FHE via significantly increased hBMSC attachment, proliferation and osteogenic differentiation with ARS and PCR analysis. Moreover, In-vivo results indicated that BP-FHE hydrogels can successfully optimize the recovery of ACLR through enhancing osteogenesis and improving the integration of tendon and bone interface. Further results of Biomechanical testing and Micro-CT analysis (bone tunnel area (mm2) and bone volume/total volume (%)) demonstrated that BP can indeed accelerate bone ingrowth. Additionally, histological staining (H&E, Masson and Safranin O/fast green) and immunohistochemical analysis (COL I, COL III and BMP-2) strongly supported the ability of BP to promote tendon-bone healing after ACLR in murine animal models.